GEMA TANGGUH Model: Integrating Early Warning and Simulation to Strengthen Early Childhood Teacher Resilience - Wijayanti, Wijayanti; Nugroho, Eko; Siswanto, Hery (Poltekkes Kemenkes Surakarta, 2025)
Background: Indonesia is among the world’s most disaster-prone countries, where early childhood education (ECE) institutions remain vulnerable due to limited preparedness and infrastructure. Teachers often lack confidence and structured procedures for emergency situations. This study aimed to evaluate the effectiveness of the GEMA TANGGUH (Movement for Mitigation and Education to Improve Disaster Response) model in enhancing the holistic resilience—cognitive, affective, and psychomotor—of ECE teachers. Methods: This university-based community service program employed a one-group pre–post test design. Eleven teachers and staff, along with 91 students from Aisyiyah Banyudono Playgroup, Boyolali, participated. The intervention consisted of interdisciplinary training on disaster mitigation, installation of IoT-based EWS, and structured evacuation simulations. The evaluation stage was conducted by collecting data through pre–post questionnaires and structured observations, which were then analyzed descriptively to determine mean score improvements and percentage changes across three evaluated domains. Results: The GEMA TANGGUH model produced substantial improvements across all domains. Teachers’ knowledge increased from an average score of 47.5 (pre) to 70.0 (post), a relative gain of 47.4%. Teachers reporting “very confident” rose from 10% to 50%. Psychomotor performance reached 100% accuracy, and student compliance achieved 98.89% (90 out of 91 students), indicating effective knowledge transfer. Conclusion: The GEMA TANGGUH model effectively strengthens comprehensive disaster preparedness among ECE teachers. Uniquely integrating IoT-based Early Warning Systems and Psychological First Aid (PFA)-oriented simulations, the model provides an evidence-based and scalable framework for building holistic resilience, supporting the advancement of disaster-resilient educational institutions in disaster-prone areas.